(3eMGSf GdJUhas - (3eMeO Hf GdMSjf Hf eMeO Hf ehSi GdCROj GdSdej GdfjSGHhQj, CHh YHO GdQMef,J (B412 (3g` s
(3ChdgG (B:s
(3bGd GdTjN GdSdei GdfjSGHhQi QVi Gddg Yfg (B: (3GdMeO ddg ChdkG hBNQkG Ef efcQG CfcQ HfG MjJce Ydi GdJUha hCgdg HEfg djS dge bOhI hdG Sda s
(3BNQgG (B:s
(3bGd GdTjN hbO NQLJ gPg GdCHhGH Ydi GdESJbUGA ai cJGH Sff GdUhajg hGddg JYGdi jMbb HaVdg WQjb GdUhGH s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B99 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B258s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs